2013
DOI: 10.1039/c3cc45418e
|View full text |Cite
|
Sign up to set email alerts
|

Between red and yellow: evidence of intermediates in a vapochromic Pt(ii) salt

Abstract: [Pt(tpy)Cl]ClO4·H2O (1·H2O) changes from red to yellow upon dehydration due to increased Pt···Pt distances. Spectroscopic, diffraction, gravimetric and calorimetric data demonstrate the presence of intermediates during hydration and dehydration which signifies surprising mechanistic complexity in the vapochromic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…4 Through the Type I mechanism, vapochromic materials exhibit color and luminescence changes by modifying intermolecular interactions on chromophores induced by vapor molecules. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In contrast, the Type II mechanism allows the generation of vapochromism from the direct coordination of vapor molecules to the chromophore, resulting in a change in the absorption/ emission energy. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Pt(II) complexes with Pt/Pt interactions (Type I mechanism) are promising candidates of vapochromic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Through the Type I mechanism, vapochromic materials exhibit color and luminescence changes by modifying intermolecular interactions on chromophores induced by vapor molecules. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In contrast, the Type II mechanism allows the generation of vapochromism from the direct coordination of vapor molecules to the chromophore, resulting in a change in the absorption/ emission energy. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] Pt(II) complexes with Pt/Pt interactions (Type I mechanism) are promising candidates of vapochromic materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably because the stabilization of adsorbed vapor molecules on almost all vapochromic Pt(II) complexes is achieved by relatively weak intermolecular interactions, such as hydrogen bonding. 6,7,[9][10][11][12]14,15,[18][19][20][21][22] Thus, the vapor-adsorbed crystal structure was not effectively stabilized, making it difficult to determine whether vapor adsorption occurred. Conversely, it is a common strategy for non-Pt(II) vapochromic complexes to provide a strong binding site, such as a coordination site, for vapor molecules to bind with the host molecules (including Type II mechanism).…”
Section: Introductionmentioning
confidence: 99%
“…This is explained by the evaporation of water, causing the rearrangement of 24 and the reinforcement of metal⋅⋅⋅metal interactions [58] . This behavior is typically observed in vapochromic complexes, which show chromism over vapor uptake/heating cycles [58,94] …”
Section: Temperaturementioning
confidence: 97%
“…Chromic materials showing reversible color change in response to external stimuli, such as heat, vapor, and mechanical pressure, have drawn considerable attention in recent years. This is because such materials enable a visualization of the invisible stimuli as a change in the color of the material. Especially, vapochromism has generated a lot of interest in the field of chemical sensors because it enables us to know the existence of invisible and harmful volatile organic compounds (VOCs). , Many vapochromic materials have been reported to date, and one of the most promising systems is that of Pt­(II) complexes with intermolecular metallophilic interactions. The color and luminescence of these complexes are strongly dependent on the degree of the interactions originating from the intermolecular 5d z orbital overlaps of the Pt­(II) ions to form the occupied antibonding dσ* orbital. In other words, even a slight modification of the crystal or the aggregated structure in this system can induce a significant change in the transition energy from the Pt···Pt dσ* orbital to the π* orbital of the organic ligand, the so-called metal–metal-to-ligand charge-transfer (MMLCT) transition, resulting in a change in the color and luminescence. , For example, Aliprandi et al reported an interesting and outstanding color change from blue to red of the amphipathic Pt­(II) complex .…”
Section: Introductionmentioning
confidence: 99%